1969
DOI: 10.1002/1097-4679(196904)25:2<221::aid-jclp2270250235>3.0.co;2-i
|View full text |Cite
|
Sign up to set email alerts
|

A survey of technician frequency and activities in clinical psychology

Abstract: Comparability of group television and individual administration of the Peebody Picture Vocabulary Teat: Implications for screening. J . due. Pqchol., 1907,68, 137-140. 6. Gum, E. V. and NIORO, M. R. Clessroom learning 88 a function of method of preaenting instructional materials. Peycliot., Rep., 1966, 19, 971-977. 7. MCGREW, J. M., MARCIA, J. E., and WRIGHT, C. K. Branc program, text, and lecture: A 8 ? m~n o~~z , G . h versus cleseroom instruction in foreign language: A study of elementary . Edue., 1964,33, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1971
1971
2012
2012

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Using a psychometrist in the field of neuropsychology has been an established standard for more than three decades (DeLuca, 1989). Brodsky and Mixon (1969) reported that 16.5% of clinical psychology service providers surveyed used psychometrists and noted that ''a growing role is being established in clinical psychology for the psychological technician'' (p. 223). By 1986, 50% of survey respondents stated that they used psychometrists in their practice (Serenty, Dean, Gray, & Hartlage, 1986).…”
Section: History Of Psychometrymentioning
confidence: 71%
“…Using a psychometrist in the field of neuropsychology has been an established standard for more than three decades (DeLuca, 1989). Brodsky and Mixon (1969) reported that 16.5% of clinical psychology service providers surveyed used psychometrists and noted that ''a growing role is being established in clinical psychology for the psychological technician'' (p. 223). By 1986, 50% of survey respondents stated that they used psychometrists in their practice (Serenty, Dean, Gray, & Hartlage, 1986).…”
Section: History Of Psychometrymentioning
confidence: 71%
“…294]." Brodsky and Mixson (1969) surveyed 224 clinical psychology departments. Thirty-seven (16.5%) reported employment of "psychology technicians."…”
mentioning
confidence: 99%
“…But Gates and Dawson did not break down the salary information into experience levels or geographical areas, as was done in the present study. Brodsky and Mixson (1969) found a mean beginning annual salary for psychology technicians of $4,361.…”
mentioning
confidence: 99%